Interactions between acoustic challenges and processing depth in speech perception as measured by task-evoked pupil response - Shen, Jing; Fitzgerald, Laura P.; Kulick, Erin R. (Frontiers in Psychology, 2022)
Speech perception under adverse conditions is a multistage process involving a dynamic interplay among acoustic, cognitive, and linguistic factors. Nevertheless, prior research has primarily focused on factors within this complex system in isolation. The primary goal of the present study was to examine the interaction between processing depth and the acoustic challenge of noise and its effect on processing effort during speech perception in noise. Two tasks were used to represent different depths of processing. The speech recognition task involved repeating back a sentence after auditory presentation (higher-level processing), while the tiredness judgment task entailed a subjective judgment of whether the speaker sounded tired (lower-level processing). The secondary goal of the study was to investigate whether pupil response to alteration of dynamic pitch cues stems from difficult linguistic processing of speech content in noise or a perceptual novelty effect due to the unnatural pitch contours. Task-evoked peak pupil response from two groups of younger adult participants with typical hearing was measured in two experiments. Both tasks (speech recognition and tiredness judgment) were implemented in both experiments, and stimuli were presented with background noise in Experiment 1 and without noise in Experiment 2. Increased peak pupil dilation was associated with deeper processing (i.e., the speech recognition task), particularly in the presence of background noise. Importantly, there is a non-additive interaction between noise and task, as demonstrated by the heightened peak pupil dilation to noise in the speech recognition task as compared to in the tiredness judgment task. Additionally, peak pupil dilation data suggest dynamic pitch alteration induced an increased perceptual novelty effect rather than reflecting effortful linguistic processing of the speech content in noise. These findings extend current theories of speech perception under adverse conditions by demonstrating that the level of processing effort expended by a listener is influenced by the interaction between acoustic challenges and depth of linguistic processing. The study also provides a foundation for future work to investigate the effects of this complex interaction in clinical populations who experience both hearing and cognitive challenges.